Evaluation of sodium levels and changes in foods from the top 20 Canadian restaurant chains (2016–2020) against UK National Salt Reduction Maximum targets - Caroline G. Middleton; Yahan Yang; Mavra Ahmed; Jennifer J. Lee; Mary R. L’Abbé (PLoS ONE, 2025)
High sodium intake contributes to hypertension, a leading risk factor for cardiovascular disease. Over 50% of Canadians regularly consume prepackaged and restaurant foods, which account for more than 70% of dietary sodium. Canada currently lacks public health strategies to address sodium levels in restaurant menu items, while the UK’s voluntary sodium reduction program (with targets set through the National Salt Reduction Initiative [NSRI]) led to significant reductions in sodium. The objectives were to compare sodium levels in Canadian restaurant menu items in 2020 to the UK NSRI 2024 targets and analyze changes between 2016 and 2020. Data were obtained from the University of Toronto Menu-FLIP (Food Label Information and Price) database, which includes over 20,000 items from 141 Canadian chain restaurants. A total of 3,616 menu items from the top 20 Canadian chains were assessed, of which 1,914 items in categories with UK NSRI 2024 targets were identified and compared to those targets, and 607 items were matched between 2016 and 2020 and analyzed for sodium changes. More than half (56.6%, n = 1,083/1,914) of items exceeded UK NSRI targets. Sodium (mg/100 g) showed a large decrease in 39.5% (n = 100/607) of items, a medium decrease in 15.8% (n = 63/607), little change in 28.9% (n = 182/607), a medium increase in 5.3% (n = 68/607), and a large increase in 10.5% (n = 194/607) from 2016 to 2020. The prevalence and magnitude of sodium changes varied by food category. Overall, there was a statistically significant but nutritionally insignificant reduction in sodium per serving from 2016 to 2020 (−24 ± 819 mg, p < 0.01). Canadian restaurant menu items were high in sodium, with more than half surpassing the UK NSRI targets. The observed increases and decreases in sodium highlight the need for Health Canada to set and for industry to adopt sodium reduction targets for restaurant menu items, similar to those in the UK.